Ecotoxicological effects of atmospheric particulate produced by braking systems on aquatic and edaphic organisms. (April 2020) - Volta, Anna; Sforzini, Susanna; Camurati, Corrado; Teoldi, Federico; Maiorana, Simone; Croce, Alessandro; Benfenati, Emilio; Perricone, Guido; Lodi, Marco; Viarengo, Aldo
Graphical abstract: Highlights: The toxicity of particles from traditional and innovative brake systems was studied. A wide range of bioassays on aquatic and edaphic model organisms was employed. Freshwater organisms were the most sensitive to particulates, also as soluble fraction. No risk for biodiversity was found, a new brake system being more eco-friendly. Sublethal effects of brake particles were found already at minimal concentrations. Abstract: Vehicles generate particulate matter (PM) in significant amounts as their brake systems wear. These particles can influence air quality and their transport/deposition may affect the edaphic and aquatic ecosystems. As part of the LOWBRASYS H2020 project, new more eco-friendly brake disc and pad formulations were developed. PMs generated from traditional (FM1-BD1) and innovative (FM4-BD2, FMB-BD7) brake systems in bench tests were studied. The PMs' physical/chemical characteristics were preliminarily investigated. To study the possible environmental impact of the nano-micro particulate, we used a battery of ecotoxicological tests. We employed the microalga Pseudokirchneriella subcapitata, the crustacean Daphnia magna and the bacteria Vibrio fischeri as aquatic bioindicators, while for the edaphic ecosystem we used the seeds of Lepidium sativum and Sorghum saccharatum, the nematode Caenorhabditis elegans, the earthworm Eisenia andrei and the ameba Dictyostelium discoideum . The results showed a higher sensitivity of the freshwater organisms exposed to the soluble PM fraction, with respect to the edaphic ones. FM4-BD2 brake formulation was slightly more toxic for algae (200 mg/L) than FM1-BD1 (500 mg/L). The new system FMB-BD7 particulate was not harmful for crustacean survival, and resulted weakly toxic for algal reproduction only at 500 mg/L. The particulate material per se was found to affect the algal reproduction. No toxic effects were found on nematodes, earthworms and seeds up to 1000 mg/L. However, in D. discoideum the reproduction rate was significantly reduced starting from 100 mg/L; and the lysosomal membrane stability showed a relevant alteration also at minimal concentration (0.1 mg/L). The results demonstrated a minimal risk for biodiversity of the particulates from the different brake systems and highlighted a more eco-friendly performance the new brake-pad FMB-BD7. However, the occurrence of sublethal effects should be considered as a possible contribution of the particle toxicity to the biological effects of the environmental pollution.